Folklore Storytelling: A Study into the Effectiveness of Traditional Short Story for Enhancing Vocabulary Development in EFL Learners - Ke Lomi, Aplonia Nelci; Aleksius, Madar; Sahan, Meylisa Yuliastuti (UIN Salatiga, 2024)
This study explores the effectiveness of integrating traditional short stories into English as a Foreign Language (EFL) instruction to enhance vocabulary development among eighth-grade students in South Amarasi. Employing a mixed-methods design, the research assesses the impact of storytelling on vocabulary acquisition by administrating pre-test and post-test assessments to 26 junior high school students. The results indicate a significant 20% improvement in vocabulary knowledge following the intervention. Qualitative insights gathered from teacher interviews reveal several critical findings. Teachers reported challenges in integrating cultural values into the teaching, particularly due to limited resources. Nonetheless, they confirmed that storytelling and visual media are instrumental in enhancing vocabulary acquisition and cultural awareness among students. The use of traditional stories not only makes learning more engaging but also helps students relate new vocabulary to their cultural backgrounds. The research highlights the pedagogical benefits of storytelling in EFL instruction and suggests that this approach effectively supports both vocabulary development and cultural literacy. The study recommends further research with larger sample sizes and cross-cultural comparisons to gain a deeper understanding of the long-term effects of storytelling on language proficiency and cultural literacy, especially in similar suburban Indonesian contexts.